Metastas is a stheexp ression of the restriction of civilization to click-time temporariness - Bańka, Józef (Folia Philosophica, 2006)
The author puts forward the thesis that the area of the “relevance” category referring to “now” will undergo a further reduction. As a result of it, man’s life will be reduced to temporariness, and, in extreme cases, one moment timed by a mouse clik, i.e. click-time. To substantiate it, the author introduces the notion of “metastasis”, i.e. transmission of values that are not the existence into the place accurate for the existence. Because these values meaning truth, good, beauty do not exist beyond references to the existence, they take on the new meaning as a result of this kind of metastasis. It concerns a clear and accurate movement of the category of the existence, truth, good and beauty from the centre of the field of vision to its outskirts, and the other way round. So, the existence “happens” as a result of clik-time metastasis I and takes on the form of the truth, as a result of click-time metastasis II and presents itself as good, and so on. The reverse order is possible, too. In such a way, the existence of our civilization is constantly moving and changing into various forms of relevance. The content of phenomena is separated from these phenomena, however, thoughts come across their content by means of a separated existence — with the power of electrical appliances — in its outskirts. It happens with the use of different levels of intensity of the sense of reality reduced to click-time can take.